In Vitro studies on antioxidant and immunomodulatory activities of Thai medicinal plants in longevity formulas - Supreeya Yuenyongsawad (Prince of Songkla University, 2021)
Thesis (Ph.D., Pharmaceutical Science)--Prince of Songkla University, 2007